The effect of active compound isolated from the leaves of kembang bulan [Tithonia diversifolia (Hemsley) A. Gray] on cell cycle and angiogenesis of WiDr cell line - Mardihusodo, Hajid Rahmadianto; Hartati Wahyuningsih, Mae Sri; Astuti, Indwiani (Universitas Gadjah Mada, 2013)
Colorectal cancer is the tenth most common form of malignant tumor of hospital inpatients inIndonesia. Advance approaches in anticancer development is discovery molecular-targeted drugs.Molecular targets for anticancer drug have been identified including genes associated with cellcycle control and angiogenesis. Previously, an active and selective compound against WiDr fromTithonia diversifolia (Hemsley) A. has been isolated. The aim of this study was to evaluate theeffect of the isolated active compound fromT. diversifolia on the WiDr cell cycle and angiogenesis.Isolation of the active compound was performed by preparative thin layer chromatography (TLC)method. WiDr cell cycle was analyzed by flowcytometry using propidium iodide (PI).Antiangiogenesis effect was evaluated by immunocytochemistry method using anti-human VEGFmonoclonal antibody. The results showed that the effect of the isolated active compound onthe WiDr cell cycle depended on the concentration and the incubation time periods. Atconcentration of 4 Î¼g/mL, it inhibited the WiDr cell cycle SubG1 phase after 36 and 48 hoursincubation and G1 phase after 72 hours incubation. While at concentration of 8 Î¼g/mL, it clearlyinhibited the WiDr cell cycle G1 phase after 36, 48 and 72 hours incubation. Furthermore, theisolated active compound at concentration of 4 Î¼g/mL significantly inhibited the VEGF expressionuntil 47.38% compared to control. In conclusion, the isolated active compound fromT. diversifoliainhibited cell cycle and angiogenesis of WiDr cell.